Osteogenesis Imperfecta (Type IV) with Dental Findings in Siblings - Shishir Ram Shetty; Deepa Dsouza; Subhas Babu; Preethi Balan (Case Reports in Dentistry)
Osteogenesis imperfecta (OI) is a hereditary disorder characterized by increased tendency for bone fractures due to high fragility. The clinical and radiological features of OI manifest in different age groups, although the disease is congenital in nature. Besides bone fragility, features like laxity of the ligaments, blue sclera, growth retardation, and scoliosis are also observed. In severe cases, respiratory distress and death have been reported. The most important oral finding in OI is the presence of yellowish-brown-coloured brittle teeth characteristic of dentinogenesis imperfecta. Genetic factors play a very important role in the pathogenesis of OI either as a dominant or recessive factor. When a child has OI, there is a 25% chance of the sibling to have the same disorder. We report two cases of OI in siblings born to parents with a history of consanguineous marriage. The clinical and radiological features of the two cases are described in detail.